Truth and Philology. Prolegomena to a critical-historicist theory of a neo-humanism (Nóema, 2011)
The Author, grounding his reflections on an accurate analysis of the work by Said and Auerbach, without forgetting the essential points laid down by Vico as an essential reference of both previous thinkers, points to the knowing method of the living philology – considered as an historical science – and intends it as an effective mean in order to develop and sustain a critical and autonomous thought, not slavish towards tradition, and oriented to the grounding core of a new humanism.
Keywords: Edward Said; Erich Auerbach; Giambattista Vico; Filologia vivente; Neoumanesimo; Pensiero critico; Interculturalità; Identità; Living Philology; Neo- humanism; Critical thought; Interculturality; Identity